Effect of intensity of physical activity on body fatness and fat - Tremblay, A.; Despres, J.; Leblanc, C.; Craig, C. L.; Ferris, B.; Stephens, T.; Bouchard, C. (The American Journal of Clinical Nutrition, 1990)
Tremblay et al (1) examined observations of 1366 women and 1257 men who participated in the 1981 Canada Fitness Survey. Subjects were tested for energy expenditure of leisure-time activities and estimated VO2 max. Body fat was measured using skinfolds and anthropometric measurements were also made. Subjects were divided into 4 subgroups based upon the METS for their leisure time activities. FINDINGS: Subjects engaging in the most intense forms of exercise had the lowest skinfolds and waist-to-hip ratios. These differences remained statistically significant after the effect of total energy expenditure of leisure-time activity on body fat and fat distribution was removed by covariance analysis. The waist-to-hip ratio also remained significantly lower for individuals engaging in high-intensity exercise after the effect of subcutaenous fat on fat distribution was accounted for.